Risk Factors for Repeated child Maltreatment - FreysteinsdUttir, F. (2004)
The purpose of this study was to identify risk factors for repeated child maltreatment in Iceland. Only cases that had never been reported to child protection services before were included in this study (N=77 total). Each case was followed for 18 months. In all cases the first reported incident was neglect. In the study, a group of cases that had only been reported once (single incident) was compared with another group of cases that had been reported two or more times (repeated incidents).